Overview of Technologies Used to Extract Scandium from Secondary Raw Materials - Orynbayev, B. M.; Baigenzhenov, O. S.; Turan, M. D. (Inst Metallurgy & Ore Beneficiation, 2024)
The exceptional mechanical and chemical properties exhibited by scandium, characterized by its low density, high strength, and remarkable resistance to corrosion, have positioned it as a sought-after metal in diverse industrial applications. Consequently, a surge in market demand for scandium has been observed, highlighting its unique attributes compared to other metals. The Republic of Kazakhstan has identified potential sources of scandium in the waste generated by the titanium, uranium, and aluminum industries. By implementing efficient processing techniques for these production wastes, the country can effectively address the deficit of scandium while also mitigating man-made emissions, thus significantly improving the environmental landscape. This article aims to explore and evaluate contemporary methodologies that have been employed for the recovery of scandium from the aforementioned secondary sources. By examining and analyzing these techniques, we can gain insights into the most effective and sustainable approaches to harnessing scandium from waste materials in Kazakhstan. This research not only contributes to meeting market demands but also ensures the responsible utilization of scandium, benefiting not just the country's economy but also its environmental sustainability.
Keywords: titanium wastes; rare metals; scandium; rare earth elements; leaching; chlorination